“Simplifying” Digital Complexity? A Socio-Technical Perspective. Editorial Introduction to Issue 33 of CSIMQ - Mikko Rajanen; Aurelio Ravarini (Complex Systems Informatics and Modeling Quarterly)
This thematic issue of four papers focuses on the importance of a socio-technical perspective in research and practice. A socio-technical perspective sees an organization as a combination of two components – a social and a technical one. The real pattern of behavior in the organization is determined by how well these parts fit each other. While analyzing system problems of getting things done, adequate consideration should be given to technology as well as informal and formal interactions of people with the technology as well as with other people using the technology. The papers in this issue present the sociotechnical perspective as a lens enabling researchers and practitioners to simplify the digital complexity in the socio-technical context.